Heating by flat plate collector combined with a heat pump - Marčič, Simon (Strojniški vestnik, 2018)
The aim of the research was to establish the efficiency of the combination flat plate collector-heat pump versus ambient air-heat pump. The extensive measurements were carried out and analysed of the flat plate collector alone and combination flat plate collector-heat pump. In the beginning, the heat pump introduction into the serial combination with flat plate collectors was analysed. The appropriate test rig with measurement equipment was designed and built. The test rig base consisted of the flat plate collector, heat pump, and 300 l boiler that was a replacement for a house`s heating. Detailed temperature measurements were performed during rainy, sunny and cloudy weather in summer and winter. To estimate the efficiency of heating, the consumed electric energy versus heat is the universal criterion that is derived from the Coefficient of performance (COP), which is calculated on the basis of measured temperatures. The comparison of the calculated COP for the combination flat plate collector-heat pump and the air-water heat pump shows that the largest increase of the COP of the combination flat plate collector-heat pump in comparison with the air-water heat pump is on sunny winter days, and that it amounts to 38 %. In rainy and cloudy weather, the COP of the flat plate collector-heat pump combination is lower than the air-water heat pump COP. The presented analyses clearly indicated that use of the flat plate collector is limited.
Keywords: flat plate collector; heat pump; ogrevanje; ploščati sončni kolektorji; preizkuševališče; test rig; the coefficient of performance; toplotne črpalke; toplotno število; učinkovitost gretja